Proceeding From in vivo Functions of Pheromone Receptors: Peripheral-Coding Perception of Pheromones From Three Closely Related Species, Helicoverpa armigera, H. assulta, and Heliothis virescens - Wang, Bing; Liu, Yang; Wang, Gui-Rong (Frontiers in Physiology, 2018)
Three closely related species, Helicoverpa armigera, H. assulta, and Heliothis virescens from Lepidoptera Noctuidae, are used as a model system for exploring sexual communication and species isolation. Pheromone receptors (PRs) previously discovered in model moth species include seven in H. armigera, six in H. assulta, and six in H. virescens. PRs named OR6, OR13, and OR16 among these species were found to be functional, characterized by an in vitro Xenopus oocytes system. Using an in vivo transgenic fly system, functional assays of OR6, OR13, and OR16 clades from three closely related Noctuidae species showed that OR13 function was highly conserved, whereas OR6 and OR16 exhibited functional divergence. Similar results were produced from assays in the Xenopus oocytes system. Combined with earlier behavioral results and electrophysiological recordings, we found corresponding relationships among pheromones, PRs, and neurons at the periphery sensory system of each species. Our results provide vital information at the neuronal and molecular level, shedding insight into the sexual communication of closely related species in Lepidoptera.